Pemberian Pupuk Kompos dan Cair Azolla terhadap Pertumbuhan dan Kandungan Flavonoid Tanaman Kedelai Hitam (Glycine max L.) - Widia Hariani; Rahmadina Rahmadina; Leni Widiarti (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Black soybean (Glycine max L.) is a food crop commodity. The low productivity of soybean in Indonesia is caused by several factors, including the availability of low-quality seeds and the unavailability of nutrients. Therefore, this study aims to determine the effect of compost and liquid Azolla fertilizer (Azolla pinnata) on the growth and flavonoid content of black soybean plants (Glycine max L.). With the factorial RAK method. The first factor is without Azolla compost fertilizer (K0), Azolla compost fertilizer 250 gr / polybag (K1), Azolla compost fertilizer 300 gr / polybag (K2). The second factor is without liquid azolla fertilizer (C0), azolla liquid fertilizer 130 ml / l of water (C1), azolla liquid fertilizer 150 ml / l of water (C2). And the data is processed using SPSS with the ANOVA test. If the treatment obtained has a very significant effect, it will be continued with the DMRT test. The results showed that Azolla compost fertilizer affected plant height, number of leaves and total leaf area with a dose of 250 gr/polybag. While Azolla liquid fertilizer did not affect all parameters at all doses, namely 130 and 150 gr/polybag. The highest flavonoid content in black soybean leaves was found in the 250gr compost fertilizer treatment, namely 99.72247 QE/g. It can be concluded that Azolla compost fertilizer is more effective in increasing the flavonoid content of black soybean leaves. The flavonoid content of the 250gr compost fertilizer treatment was 99.72247 QE/g in the leaves.